Apparent spontaneous regression of malignant neoplasms after radiography: Report of four cases. (2016) - Sasaki, Jun; Kurihara, Hideo; Nakano, Yoshishige; Kotani, Kohji; Tame, Eisuke; Sasaki, Akira
Highlights: On rare occasions, apparently spontaneous regression of unknown etiology is observed in a neoplasm. We report a series of 4 patients with apparent spontaneous regression of malignant neoplasms after radiography. Apparently spontaneous regression of these malignant lymphomas and cancers was caused by the small radiation doses received in the radiographic examinations. Abstract: Introduction: On rare occasions, an apparently spontaneous regression of unknown etiology is observed in a neoplasm. We report a series of 4 patients with apparent spontaneous regression of malignant lymphomas after radiography. Presentation of case: All four of the tumors were malignant lymphomas. The regressions occurred between 1 and 2 months after the radiographic examinations. All four patients later underwent relapse and needed additional treatments: surgery, chemotherapy and/or radiation. Discusssion: Four cases had the following features in common: (1) the neoplasms were radiosensitive, (2) the regression occurred after radiography, (3) none of the neoplasms was in the advanced stage, and (4) the doses received through radiographic exposure were a little higher than usual because CT was included for most of the patients. Conclusion: We suspect that the apparently spontaneous regression of malignant lymphomas was caused by the small radiation doses received in the radiographic examinations.